Analysis of Mathematic Problem-Solving Ability in Solving Pythagoras Theorem Problems - Nafisah, Zawahir; Husna, Laila Diyatul; Khayroiyah, Siti (Riemann: Research of Mathematics and Mathematics Education, 2024)
Problem solving is about finding a solution to a problem, so learning mathematics involves solving problems that relate to everyday life. The method of research used is qualitative descriptive research aimed at describing and explaining the methods of solving problems of Pythagoras's theorem students, as seen from the analysis of student's ability to solve mathematical problems. Information obtained from the work or written answers (tests) that have been completed. In this study, 30 students participated in the 2022/2023 academic year in the eighth grade of Delitua Private High School. The highest percentage value was 98.04% for the indicator of problem understanding, while the lowest percentage was 33.34% for the re-examination indicator. Overall, the average percentage score was 69.51%, which is high. This means that the ability of the students of the eighth grade of Delitua Private High School to solve mathematical problems using the material of Pythagoras's theorem is very competent. The students' responses to the statement in the mathematical problem-solving test were effective because all the statements were answered positively by ≥ 90% of students